Confirmation of β-agonist residues in bovine retina and liver using HPLC-MS/MS and evaluation of matrix-dependent problems. Issue 4 (3rd April 2017) - Regal, Patricia; Díaz-Bao, Mónica; Barreiro, Rocío; Vázquez, Beatriz I.; Cepeda, Alberto
ABSTRACT: β-Agonists or β-adrenergic agonists are synthetic drugs sometimes used for therapeutic purposes in veterinary medicine. However, these compounds also belong to a class of illegal growth promoters that decrease the fat content in farm animals. The purpose of this study was to develop an analytical LC-MS/MS confirmatory method for the detection of nine β-agonists in bovine retina and liver tissues. The obtained CCα values ranged from 0.29 to 1.54 µg kg – 1 in retina and from 0.03 to 0.18 µg kg – 1 in liver, and CCβ values from 0.50 to 2.63 µg kg – 1 and from 0.05 to 0.30 µg kg – 1, respectively. Additionally, the importance of a matrix effect in these two tissues for the achievement of accurate detection of non-compliant samples was studied and discussed. It was concluded that the main characteristic of this phenomena is its considerable variability from one animal to another. Also, the total amount of matrix in the final extract can provide differences in the matrix-matched calibration line.